The Effects of a Professional Development Program on the Classroom Practices of Physics Teachers - Ozlem Oktay; Ali Eryilmaz (Journal of Education in Science, Environment and Health)
The purpose of the study is to examine the effects of a long-term professional development (PD) program on the classroom practices of physics teachers. Changes in teachers’ practices were investigated across four dimensions: content, teaching strategy, materials/technology, and assessment. The present study used qualitative research methodology, including a case study research. Data were collected from seven participating teachers and their 9th grade students. The PD model framework has four main components: analysis, planning, implementation, and evaluation. A teacher survey, an observation form, a student group-interview protocol, treatment-fidelity and treatment-verification opinion forms were developed as measuring instruments. Thematic coding was used in every dimension. The data were evaluated using a frequency analysis and displayed in tables. The results showed that the PD program had a positive effect on teachers’ classroom practices. The more the teachers participated in each dimension of the PD program, the greater the level of positive change observed in the teachers’ lesson applications. When the results were examined in relation to teaching strategies, materials/technologies, and assessment techniques used for various purposes, there was a clear increase in the number, variety, and quality of strategies, materials, and technologies used in these dimensions.